2011
DOI: 10.3354/aei00033
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent, stratified flow through a suspended shellfish canopy: implications for mussel farm design

Abstract: Observations were used to quantify the influences of turbulent flow and mixing through the suspended canopy formed by a shellfish aquaculture farm in the microtidal Danish Limfjorden. Observations included current meter/profiler timeseries data and turbulence microstructure profiling. The influence was 2-way in that the turbulence is partially driven by the canopy and in turn the canopy is affected by the turbulence. The canopy reduced the flow speeds within its interior, which was sufficient to reduce levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 36 publications
1
32
0
Order By: Relevance
“…Current velocities measured inside the farm were used to account for the effect of mussel structure drag on currents (Cranford et al 2014). Current speeds within the farm averaged 0.027 m s −1 and are in accordance with previously measured current speeds in and around mussel farms in Skive Fjord (Stevens & Petersen 2011). Published CR values for individual M. edulis of standard size vary over a wide range, owing largely to responses to ambient food concentration and composition; in situ CR measurements can differ greatly from the theoretical maximum (e.g.…”
Section: Depletion Modelsupporting
confidence: 79%
See 1 more Smart Citation
“…Current velocities measured inside the farm were used to account for the effect of mussel structure drag on currents (Cranford et al 2014). Current speeds within the farm averaged 0.027 m s −1 and are in accordance with previously measured current speeds in and around mussel farms in Skive Fjord (Stevens & Petersen 2011). Published CR values for individual M. edulis of standard size vary over a wide range, owing largely to responses to ambient food concentration and composition; in situ CR measurements can differ greatly from the theoretical maximum (e.g.…”
Section: Depletion Modelsupporting
confidence: 79%
“…Increasing the mussel biomass within the mussel farm would, on the other hand, cause additional flow reduction (e.g. Petersen et al 2008, Stevens & Petersen 2011, Cranford et al 2014, which would increase water re-filtration by the mussels and reduce realized CRs, growth rates and nutrient extraction. Increasing mussel density may therefore be expected to reach a self-limited threshold for the extraction of excess phytoplankton that is specific to a given area.…”
Section: Discussionmentioning
confidence: 99%
“…By comparison, production of Laminaria hyperborea has been reported to be as high as 3000 g C m −2 (Abdullah & Fredriksen 2004). We have not taken into consideration the effects of the fish and kelp farms themselves on the water currents, which may reduce the fluxes of nutrients within the IMTA system (Grant & Bacher 2001, Plew 2011, Stevens & Petersen 2011. Neither have we considered small-scale reduction in DIN concentrations around single kelp ropes due to crowding of the plants.…”
Section: Simulation Experiments and Implications For Imtamentioning
confidence: 99%
“…The flux of particles into the culture will depend not only on particle concentration but also on current velocity, which is affected by the culture unit structures and the mussels themselves by creating turbulence (e.g. Strohmeier et al 2005;Plew 2011;Stevens and Petersen 2011). The effect of the farm structure on the water column is mainly a modification of the flow pattern, stratification and turbulence in and around the shellfish canopy, but it has been shown that in Danish waters, culture units were not able to mix the water column and disturb stratification (Stevens and Petersen 2011).…”
Section: Additional Ecosystem Goods and Servicesmentioning
confidence: 99%